Chemical and functional properties of roasted spitting cobra (N. nigricollis) - Ogungbenle, HN; Adaraniwon, PT (Bangladesh Journal of Scientific and Industrial Research, 2013)
The proximate, nutritionally valuable minerals, amino acids and functional properties of roasted spitting cobra (Naja nigricollis) were studied. The results show that the sample contains 6.36% moisture, 79.45% crude protein, 6.35% fat and 2.96% carbohydrate. The highest mineral was phosphorus with 160.96mg per 100g and the sample was low in copper, chromium and cobalt. The protein solubility was minimum at pH 4.0 and maximum at pH 8.0. The total amino acid in the sample was 76.84g/100g protein while the total essential amino acid in the sample was 35.53g/100g protein. The sample also exhibits 9.28% water absorption capacity, 118.83% oil absorption capacity, 11% foaming capacity, 2% foaming stability, 30% emulsion capacity, 70% emulsion stability, 30% of least gelation concentration. DOI: http://dx.doi.org/10.3329/bjsir.v48i3.17331 Bangladesh J. Sci. Ind. Res. 48(3), 197-200, 2013